Spirit of '67: The Cardiac Kids, El Birdos, and the World Series That Captivated America - Whalen, Thomas J. (Rowman & Littlefield Publishers, 2017)
Using the colorful and tumultuous 1960s as a backdrop, acclaimed author Thomas J. Whalen’s Spirit of ’67: The Cardiac Kids, El Birdos, and the World Series That Captivated America shows how the Red Sox and Cardinals waged an epic battle for baseball supremacy that captured the imagination of weary Americans looking for escape from the urban riots, racial turmoil, and antiwar protests that were roiling 1960s society. “How many people ever do anything that makes so many people happy?” Sox pitcher Gary Bell asked years later, in reference to their classic autumn clash. The book examines the unique bond that each team had with its own fanbase, going back to each franchise’s chaotic beginning at the turn of the twentieth century. Relating issues of ethnicity, politics, class, and economics, Whalen sets out to reveal the exactly what was at stake in the 1967 fall classic, and how echoes from that unforgettable season still ring through both cities, and American culture, to this day.